(untitled) (Journal of the College of Basic Education, 2022)
A person with mental fitness and an innovator is considered a person who is able to resist the process of staying within the traditional frameworks of thinking and problem solving. Therefore, mental fitness achieves success in personal and professional life and is a way of dealing with life with ease and flexibility. Academic adaptation to the individual’s self-acceptance and sense of belonging. Since the university is a social environment that includes a number of individuals, the individual’s sense of satisfaction and satisfaction with the quality of university life can be reflected in its production and achievement. This research aims to know: 1-The level of mental fitness of university students. 2-The level of academic adaptation among university students. 3- The correlation between mental fitness and academic adjustment. The current research sample consisted of (400) male and female students from the faculties of Al-Mustansiriyah University, (200) males and (200) females, distributed by (200) scientific specialization and (200) human specialization, the researcher applied to them the mental fitness scale that It was prepared (Sahib, 2016) and the Baker and Cirque scale (1989) academic adaptation, and after extracting the psychometric properties of both scales through (apparent and structural validity and discriminatory power), and after applying the two scales to the current research sample, the researcher reached the following results. University students enjoy mental fitness. University students enjoy academic adaptation. 3. There is a statistically significant correlation between mental fitness and academic adaptation among university students